Reatividade em meio básico de alumina fora da rede em zeólitas ultra-estáveis - Calsavara, Valmir (1995)
This work reports studies upon the reinsertion of non-framework aluminium in ultra-stable Y zeolites by means of alkaline treatment. Two starting zeolites were prepared by ammonium-exchange of a NaY, with subsequent hydrothermal treatment at different temperatures, 823 and 923 K, generating zeolites with structural silica-to-alumina ratios (SAR) respectively equal to 8.4 and 12.1. These zeolites were treated with NaOH solution at various temperatures and contact times. The solid phase was separated by filtration and dried, being characterized by several techniques. Filtrate analysis by atomic absorption spectroscopy showed the fast solubilization of the non-framework aluminium species and their subsequent transference to the solid phase, at a rate that increases with both increasing temperature and dealumination degree of the tarting zeolite.The reduction in the structural SAR determined by 29Si RMN and FTIR confirmed the reinsertion of this aluminium in the crystalline structure. The mesoporosity reduction as seen by nitrogen adsorption points to a reinsertion in the structural defects. However, the increasing silicon solubilization after longer times of treatment raises the possibility of isomorphic substitution. The data fitting to a basic zeolite crystallization model made it possible to estimate the activation energy for the reinsertion process. The comparison of the results to the crystallization and dealumination phenomena indicated that the reinsertion is a more easily-occuring process than those ones.